(untitled) (Research, Society and Development, 2024)
Introduction: Palliative care is an expanding approach in Brazil, constituting a set of interventions that aim to provide comprehensive care to patients and families facing serious or incurable illnesses. They should therefore be considered as a relevant component of medical education, due to their impact on decision-making and the doctor-patient relationship. Objective: Discuss the importance of teaching palliative care in undergraduate Medicine. Methodology: The study was carried out through an integrative literature review, with descriptive analysis, carried out using the PICO strategy, with access to the Virtual Health Library (VHL) databases. Articles with full text and abstract, available free of charge in English, Spanish and Portuguese, from January 2017 to October 2023 were included. Results and Discussion: 7 publications were included in the study. Teaching palliative care is essential for improving quality of life and managing suffering. However, the results demonstrated gaps in the teaching of PCs, including a lack of knowledge about its basic principles, identification and treatment of symptoms, and issues involving the finiteness of life. Furthermore, the emphasis on the biomedical model makes it difficult to prepare students for palliative interventions, particularly end-of-life care. Conclusion: Despite efforts to strengthen the teaching of PCs, they are still not prioritized in medical education. Therefore, there is an urgent need for greater visibility on this topic during the academic training of future doctors, so that PCs are incorporated into care actions.